Occupational asthma: an assessment of diagnostic agreement between physicians. Issue 3 (9th November 2006) - Fishwick, David; Bradshaw, Lisa; Henson, Mandy; Stenton, Chris; Hendrick, David; Burge, Sherwood; Niven, Rob; Warburton, Chris; Rogers, Trevor; Rawbone, Roger; Cullinan, Paul; Barber, Chris; et al.
Abstract : Objectives: To investigate the levels of agreement between expert respiratory physicians when making a diagnosis of occupational asthma. Methods: 19 cases of possible occupational asthma were identified as part of a larger national observational cohort. A case summary for each case was then circulated to 12 physicians, asking for a percentage likelihood, from the supplied information, that this case represented occupational asthma. The resulting probabilities were then compared between physicians using Spearman's rank correlation and Cohen's κ coefficients. Results: Agreement between the 12 physicians for all 19 cases was generally good as assessed by Spearman's rank correlation. For all 66 physician–physician interactions, 45 were found to correlate significantly at the 5% level. The agreement assessed by κ analysis was more variable, with a median κ value of 0.26, (range –0.2 to +0.76), although 7 of the physicians agreed significantly (p<0.05) with ⩾5 of their colleagues. Only in one case did the responses for probability of occupational asthma all exceed the "on balance" 50% threshold, although 12 of the 19 cases had an interquartile range of probabilities not including 50%, implying "on balance" agreement. The median probability values for each physician (all assessing the identical 19 cases) varied from 20% to 70%. Factors associated with a high probability rating were the presence of a positive serial peak expiratory flow Occupation Asthma SYStem (OASYS)-2 chart, and both the presence of bronchial hyper-reactivity and significant change in reactivity between periods of work and rest. Conclusions: Despite the importance of the diagnosis of occupational asthma and reasonable physician agreement, certain variations in diagnostic assessment were seen between UK expert centres when assessing paper cases of possible occupational asthma. Although this may in part reflect the absence of a normal clinical consultation, a more unified national approach to these patients is required.